Study on the durability of solidified mud under chloride and dry-wet coupling - Songtao, Zhang; Jianyong, Pang; Jinsong, Zhang; Changwei, Zhou; Yaxing, Wang (Scientific reports, 2025)
In order to study the durability of solidified waste mud, dry-wet cycle experiments were carried out under the erosion of sodium chloride solutions with different concentrations. The unconfined compressive strength and mass change rate of solidified mud were studied and analyzed. The results show that when the number of dry-wet cycles increases, the unconfined compressive strength and mass of the sample show a downward trend. The unconfined compressive strength of the solidified mud in 40 g / L sodium chloride solution decreases the most, reaching 52.89%, and the mass loss reaches 8.36 g. The microstructure analysis was carried out by scanning electron microscopy. It was found that the hydration products such as hydrated calcium silicate gel ( C-S-H ) and calcium hydroxide crystal ( C-H ) in the solidified mud samples under the coupling of chloride erosion and dry-wet cycle were reduced, and more pores and cracks appeared. Under the same number of dry-wet cycles, the higher the concentration of sodium chloride solution, the more serious the micro-damage inside the sample. The decrease of the strength of the solidified slurry is due to the hydrolysis of the hydration products in the solidified mud under the combined action of chloride salt and dry-wet cycle, and some of the materials are dissolved, resulting in more cracks.